2013
DOI: 10.1111/1753-0407.12089
|View full text |Cite
|
Sign up to set email alerts
|

Obesity phenotypes and subclinical cardiovascular diseases in a mixed‐ancestry South African population: A cross‐sectional study (南非混合血统人群的肥胖表型与亚临床心血管疾病:一项横向研究)

Abstract: Keywords: cardiovascular risk factors, obesity phenotype, South Africa, sub-clinical cardiovascular disease.Efforts to characterize the disease risk associated with obesity 1 suggest that related metabolic abnormalities are not uniform in all obese persons. The concepts of "metabolically-healthy-" and "metabolicallyabnormal-" normal-weight, overweight and obese have been used to characterize the phenotypes resulting from the cross-classification of individuals by body mass index (BMI) and metabolic status. 2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…A better proxy for visceral adipose tissue is WC and, unsurprisingly, within BMI categories, participants with compared to without metabolic abnormalities had greater WC and elevated HOMA-IR index, a proxy measure of insulin resistance. Similar findings have also been reported in other studies [ 20 , 23 , 24 , 25 ]. Recent studies in Caucasians that have included insulin resistance among abnormal metabolic traits, have reported high prevalence of metabolically abnormal phenotypes both in obese and non-obese people [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A better proxy for visceral adipose tissue is WC and, unsurprisingly, within BMI categories, participants with compared to without metabolic abnormalities had greater WC and elevated HOMA-IR index, a proxy measure of insulin resistance. Similar findings have also been reported in other studies [ 20 , 23 , 24 , 25 ]. Recent studies in Caucasians that have included insulin resistance among abnormal metabolic traits, have reported high prevalence of metabolically abnormal phenotypes both in obese and non-obese people [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of body size phenotypes in our study is comparable with results of local studies conducted in the general population in South Africa [ 24 , 28 ]. Our previous community-based study in mixed-ancestry adults in Cape Town applying the same definition criteria found OMH and NWMA to be present respectively 16.5% and 5% of the sample [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study is among the firsts to examine the concept of metabolically healthy obesity in African populations, and is relevant to the ongoing debate on the usefulness of this concept. The prevalence of body size phenotypes among African populations including the urban rural differences, have seldom been investigated in studies [ 6 ]. Compared to studies conducted in other continents, and despite differences in the definitions of “metabolically healthy” that have been used, the prevalence of metabolically healthy obese individuals is similar between the present and previous studies, which found a prevalence of 6 to 75% [ 6 ], depending on the definition used, and higher in population of Asia descend than in Caucasian.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing prevalence of obesity in Africa population [ 5 ], assessment of the aforementioned body size phenotypes and their implications for disease risk and prognostic have mainly been conducted in Western populations [ 6 ]. Furthermore, few extant studies have examined the frequencies of various phenotypes by ethnicity, with suggestion of higher prevalence of metabolically healthy obesity among Asians populations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%